Cherry leaf spot incidence on 12 sweet cherry cultivars in integrated production - Vámos, A.; Holb, I. J. (International Journal of Horticultural Science, 2013)
The aim of this study was to evaluate the cherry leaf spot (CLS) incidence on 12 sweet cherry cultivars in integrated sweet cherry production in three consecutive years from 2010 till 2012. Assessed cultivars (cvs.) were ’Aida’, ’Axel’, ’Biggareau burlat’, ’Blaze Star’, ’Celeste’, ’Germersdorfi 3’, ’Izabella’, ’Katalin’, ’Krupnoplodnaja’, ’Linda’, ’Sunburst’, ’Vera’Results showed that year had an essential effect on the CLS disease incidence. Cultivars showed great differences within years. Cultivar ’Celeste’ showed the lowest disease incidence on leaves in all years lower than 10%. The largest disease incidence on leaves was on cv. ’Sunburst’ in 2010, on cv. ’Germersdorfi 3’in 2011 and on cv. ’Axel’ in 2012. Disease incidence on these cultivars ranged between 10 and 25%.